Kara za kradzież w klasycznym prawie islamu (prawie szariatu) - Knych, Adam (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
This paper is devoted to the penalty provided for theft (Hadd punishment) in classical Islamic law, i.e. Sharia law. The paper presents the basis of the punishment of amputation for this crime coming from the Qur’an as well as other detailed regulations concerning it, coming from Sunnah. The paper provides an overview of the views of Mohammedan scholars who are commentators of the Qur'an, and statements about this punishment attributed to Muhammad. The work also describes exclusions from the application of this penalty due to the perpetrator or the circumstances of the theft, as well as the possibility of avoiding this penalty. An additional element of the paper is the calculation of the minimum value of the stolen item, allowing for the execution of the Hadd penalty, taking into account today's prices of goods given in the relevant hadiths.
Keywords: Koran; prawo szariatu